Аналіз підходів у виявленні аномалій в зображеннях оптичного моніторингу - Мельніченко, Ф. О. (ХНУРЕ, 2024)
In today's world, image processing and analysis from optical monitoring sources is an important area of research due to its wide range of applications. Analyzing such images poses a major challenge for researchers and scientists due to the high variability, low resolution, and large volume of satellite imagery data. One of the fundamental tasks of image analysis from optical monitoring sources is anomaly detection. Anomaly detection in optical monitoring images (satellites, drones, unmanned aerial vehicles) is an important area of remote sensing and geospatial analysis that uses advanced algorithms and machine learning models to detect unusual patterns or changes in data that deviate from the norm. This capability is essential for a wide range of applications, from environmental monitoring and urban planning to military defense, reconnaissance and disaster response. In this article, we will look at common anomaly detection methods and technologies.
Keywords: оптичний моніторинг; виявленні аномалій в зображеннях